Kebijakan Pemerintah Provinsi Sumatera Utara Untuk Usaha Mikro Kecil dan Menengah dalam Masyarakat Ekonomi Asean - Evi Yunita Kurniaty (Mahesa Research Center, 2020)
n this study, it is focused on analyzing the political economy policy of the North Sumatra Provincial Government in the Asean Economic Community (AEC) towards Micro, Small and Medium Enterprises (MSMEs). This research was conducted with the aim to see the validity of the ideology of liberalism on the political economy policy of the North Sumatra Provincial Government in the AEC for MSMEs in North Sumatra. The method used in this research is descriptive qualitative which emphasizes the policy of the Government of North Sumatra Province in the AEC, opportunities and obstacles that arise for MSMEs. The results of this study are expected to be a reference and solution for the Government of the Province of North Sumatra in making policy for Micro Small and Medium Enterprises in running the Asean Economic Community. The resulting political policy is a policy that can take advantage of opportunities and answer the challenges that exist in the AEC. With government political policies that are right on target, they will realize shared development goals.